Efektivitas Pembelajaran Daring Mata Kuliah Mku Bahasa Indonesia Pada Mahasiswa Universitas Hamzanwadi Pada Masa Pandemi Covid-19 - Ramlah H.A. Gani; Titin Ernawati; Nunung Supratmi; Herman Wijaya; Nurdin (STKIP Al Islam Tunas Bangsa dan HEPI, 2023)
This research is a qualitative descriptive study to describe the effectiveness of learning Indonesian MKU courses using online technology for Informatics Education Study Program students at Hamzanwadi University in 2022. Online learning uses the Google Meeting, Zoom Meeting, WhatsApp, and LMS platforms. Sources of data in the form of questionnaires or questionnaires and interviews. The data collection technique uses a questionnaire technique with 45 respondents and the interview technique includes several stages, namely data reduction, data display, and drawing conclusions. Based on the results of the study, online learning in MKU Indonesian courses uses laptop technology 60% and mobile phones 40%, while the percentage of students using learning platforms prefers to learn using Zoom Meetings with a percentage of 50%, Google Meetings 30%, LMS 10%, and WhatsApp 10%. While the effectiveness of online learning methods, 60% of students stated that they were very effective, and 31% were less effective, and 8% were not effective. While the results of interviews 90% of students chose to study online, and 10% chose offline. From the results of the data, it was concluded that online learning was very effective in MKU Indonesian courses during the Covid-19 pandemic.